Assessment of vaccine wastage in the immunization clinic attached to S. P. Medical College, Bikaner, Rajasthan - Sharma, Gaurav; Sethia, Renu; Acharya, Rekha; Meena, Ratti Ram (International Journal Of Community Medicine And Public Health, 2017)
Background: India released its first National Vaccine Policy in 2011. The country is presently developing new strategies to increase immunization coverage and reach more children with quality vaccine. High vaccine wastage increase vaccine demand and inflate overall program cost. Methods:This was records based descriptive study carried out at Immunization Clinic, Sardar Patel Medical College, Bikaner, Rajasthan. The information regarding vaccine vials used at Immunization Clinic and children vaccinated were retrieved from Immunization register for the reference period 1st April 2014 to 31st March 2015. Results: Among individual vaccine, wastage factor and rates was highest (1.42 and 29.45% respectively) for Oral Polio Vaccine (OPV) and lowest (1.10 and 9.21% respectively) for Hepatitis-B vaccine. The wastage rate for multi-dose vial was 27.66% for 5 doses vial, 13.88% for 10 doses vial and highest 29.45% for 20 doses vials. Among vaccines wastage rate of lyophilized vaccines (23.30%) were higher when compared to liquid vaccines (20.66%). Conclusions:Vaccine wastage rate can be obtained by monitoring of the immunization centre. Monitoring vaccine wastage will help not only to improve quality of the programme but it will also increase the efficiency of the programme. This can thus help save significant funds for an immunization programme.